Ophthalmology secrets - Gault, Janice A. (Philadelphia, PA : Elsevier, 2023)
"For more than 30 years, the highly regarded Secrets Series® has provided students and practitioners in all areas of health care with concise, focused, and engaging resources for quick reference and exam review. Ophthalmology Secrets, 5th Edition, offers practical, up-to-date coverage of the full range of essential topics in this dynamic field. This highly regarded resource features the Secrets' popular question-and-answer format that also includes lists, tables, pearls, memory aids, and an easy-to-read style - making inquiry, reference, and review quick, easy, and enjoyable." --
"Questions you will be asked, Top secrets in ophthalmology" -- from cover
Includes bibliographical references and index
Keywords: Ophthalmology -- Examinations, questions, etc; Ophthalmology -- Miscellanea; Eye -- Diseases -- Miscellanea; Eye Diseases.(uri) http://id.nlm.nih.gov/mesh/D005128